A Phenomenological Study of College Faculty Experiences Derived from Teaching in a Computer-Mediated Environment When There is an Absence of Physical Presence - Simone Conceicao-Rulee (Adult Education Research Conference, 2001)
This phenomenological study investigated the meaning of the online teaching experiences of college faculty when there was an absence of physical presence. Findings suggest that teaching online is work intensive because of the length of engagement before and during instruction and the depth of engagement during the delivery of a course; however, it is also rewarding when the instructor experiences satisfaction throughout the process of design and delivery of instruction.